A Rhythm of Bodies: Making the Impossible Plausible Through Physicality, Risk and Trust in A Simple Space - Kristy Seymour (Circus: Arts, Life & Sciences)
Circus artists embrace the desire to achieve the impossible through exploration of the possibilities of the body. In the Australian milieu, contemporary circus performers put their bodies, their creativity and often their political agendas on the line. Contemporary circus relies on creative and ideological risk just as much as the physical risk encountered in the execution of tricks. Nevertheless, it is the body that is central to the risk explored within circus performance. In this article, I will position my theory of “A rhythm of bodies,” which explores how notions of embodiment, as well as creative and physical risk, play out in the works of award-winning and internationally renowned Adelaide-based circus company Gravity and Other Myths—how impossibility is made plausible through risk and authenticity on stage. Looking to Gilles Deleuze and Félix Guattari’s concept of a “body without organs” and Jondi Keane’s “Embodied cognition is a special kind of movement,” I will argue that in circus, bodily “impossibilities,” or the usual limitations of the body, are effectively disregarded. In drawing their own greatly extended limitations and boundaries around their bodies, circus performers do not—indeed, cannot—subscribe to the limitations that most people accept as normal. This article will discuss how circus artists use their bodies to explore the extremities of not only what a body can do, but also what a body can say.